Factores de riesgo psicosocial en adolescentes infractores de la ley penal en el barrio las Margaritas de la ciudad de Quibdó - Hurtado Martínez, Laura Victoria (Universidad Antonio Nariño, 2022)
Introduction: as established in the “Childhood and Adolescence Code, a minor offender of criminal law is considered to be anyone who has incurred in the commission of a punishable act classified as a crime or offense in criminal law. (Law 1098 2006). Objective: to understand the personality of the adolescent offender of the criminal law, from the analysis of the psychosocial risk factors that influence their antisocial and criminal behavior. Material and method: descriptivelevel phenomenological research design and qualitative approach. In the information gathering process, participant observation and in-depth interviews were used. That is, behaviors were observed and the responses of the interviewees were recorded. Results: The results show the diversity and complexity of the psychosocial risk factors in the adolescent offender and their incidence in the structuring of a narrative of aggressiveness and recognition, to the point of enjoying exercising cruel acts or causing harm to third parties, such as a shows their personality disorders that are detrimental to society. There are factors related to low self-esteem, non-assertive communication, dissemination of violent and aggressive content in the media, emotional disturbances; intra-family and / or marital conflicts; poverty, social marginalization; ease of access to weapons and friends who practice crime. Along with this, the consumption of alcohol from the age of 13; they are high-risk aspects for adolescents, which can influence their behavior and turn them into a social problem. Discussion: It is possible to understand the personality of the adolescent offender of the Criminal Law from the analysis of the psychosocial risk factors that affect his antisocial and criminal behavior, but it is not linear nor can this personality be homogenized, given that the findings register Narcissistic, sadistic, antisocial, alcoholic, aggressive, dysthymia, psychotic, and histrionic personalities.